Artificial Intelligence Technologies and the Evolution of Web 3.0 - Issa, Tomayess; Isaias, P. (IGI Global, 2015)
Web technologies have become a vital element within educational, professional, and social settings as they have the potential to improve performance and productivity across organizations.Artificial Intelligence Technologies and the Evolution of Web 3.0 brings together emergent research and best practices surrounding the effective usage of Web 3.0 technologies in a variety of environments. Featuring the latest technologies and applications across industries, this publication is a vital reference source for academics, researchers, students, and professionals who are interested in new ways to use intelligent web technologies within various settings